Remote Ischemic Preconditioning for the Prevention of Contrast-Induced Acute Kidney Injury in Diabetics Receiving Elective Percutaneous Coronary Intervention - Balbir Singh, Gillian; Ann, Soe Hee; Park, Jongha; Chung, Hyun Chul; Lee, Jong Soo; Kim, Eun-Sook; Choi, Jung Il; Lee, Jiho; Kim, Shin-Jae; Shin, Eun-Seok (PLOS ONE, 2016)
Objective Remote ischemic preconditioning (RIPC) induces transient episodes of ischemia by the occlusion of blood flow in non-target tissue, before a subsequent ischemia-reperfusion injury. When RIPC is applied before percutaneous coronary intervention (PCI), the kidneys may be protected against ischemia-reperfusion injury and subsequently contrast-induced acute kidney injury (CI-AKI). The aim of this study was to evaluate the efficacy of RIPC for the prevention of CI-AKI in patients with diabetes with pre-existing chronic kidney disease (CKD) undergoing elective PCI. Methods This randomized, double-blind, sham-controlled study enrolled patients with diabetes scheduled for elective PCI with eGFR ≤60 ml/min/1.73 m2 or urinary albumin creatinine ratio of >300 mg/g to receive either RIPC or the sham ischemic preconditioning. Results One hundred and two patients (68.9 ± 8.2 years old, 47.1% men) were included. Baseline eGFR, creatinine and serum NGAL was similar between RIPC and control groups (48.5 ± 12 ml/min vs. 46.6 ± 10 ml/min, p = 0.391; 1.42 ± 0.58 mg/dl vs. 1.41 ± 0.34 mg/dl, p = 0.924; and 136.0 ± 45.0 ng/ml vs. 137.6 ± 43.3 ng/ml, p = 0.961, respectively). CI-AKI occurred in 13.7% (14/102) of the total subjects, with both RIPC and control groups having an equal incidence of 13.7% (7/51). No significant differences were seen in creatinine, NGAL, cardiac enzymes (troponin T, CKMB) and hs-CRP between the groups post-procedure. Conclusions In this study, RIPC applied prior to elective PCI was not effective in preventing CI-AKI in patients with diabetes with pre-existing CKD. Trial Registration ClinicalTrials.gov NCT02329444